Selective metal recovery from ternary lithium-ion battery cathodes via potential-controlled electrodeposition in deep eutectic solvents - Chang, Chih-Min; Kuan, Wei-Fan (Separation and purification technology, 2025)
This study presents a potential-controlled electrodeposition strategy for selectively recovering nickel (Ni), cobalt (Co), and manganese (Mn) from leachates of ternary lithium-ion battery cathodes using a choline chloride (ChCl)-urea deep eutectic solvent (DES). Results demonstrate that remarkable leaching efficiencies for all target metals (91.2 %, 99.0 %, and 95.7 %, for Ni, Co, and Mn, respectively) were successfully achieved at 150 ℃. Upon cooling, it is observed that a majority of Ni2+ was separated through spontaneous precipitation, enabling preliminary fractionation of the leachate. Sequential electrodeposition at −1.1 V, −1.75 V, and −0.8 V facilitated the selective recovery of Co, Mn, and Ni, respectively, with high purity confirmed by structural and elemental analyses. Compared to conventional recycling methods, this approach enables efficient metal separation without the need for additional chemical additives and within relatively short electrodeposition time (2 h). These findings highlight a practical route for developing additive-free, energy-efficient, and environmentally friendly recycling technologies for spent lithium-ion battery cathodes using DES systems.